Genetic evidence for an essential role of neuronally expressed IL-6 signal transducer gp130 in the induction and maintenance of experimentally induced mechanical hypersensitivity in vivo and in vitro - Constantin Cristina E; Vogl Christian; Quarta Serena; Üçeyler Nurcan; Sommer Claudia; Kress Michaela (SAGE Publishing, 2011)
Abstract Tenderness and mechanical allodynia are key symptoms of malignant tumor, inflammation and neuropathy. The proinflammatory cytokine interleukin-6 (IL-6) is causally involved in all three pathologies. IL-6 not only regulates innate immunity and inflammation but also causes nociceptor sensitization and hyperalgesia. In general and in most cell types including immune cells and sensory neurons, IL-6 binds soluble μ receptor subunits which heteromerizes with membrane bound IL-6 signal transducer gp130. In the present study, we used a conditional knock-out strategy to investigate the importance of signal transducer gp130 expressed in C nociceptors for the generation and maintenance of mechanical hypersensitivity. Nociceptors were sensitized to mechanical stimuli by experimental tumor and this nociceptor sensitization was preserved at later stages of the pathology in control mice. However, in mice with a conditional deletion of gp130 in Nav1.8 expressing nociceptors mechanical hypersensitivity by experimental tumor, nerve injury or inflammation recovery was not preserved in the maintenance phase and nociceptors exhibited normal mechanical thresholds comparable to untreated mice. Together, the results argue for IL-6 signal transducer gp130 as an essential prerequisite in nociceptors for long-term mechanical hypersensitivity associated with cancer, inflammation and nerve injury.